Avoidance and Management of Stomal Complications - Kwiatt, Michael; Kawata, Michitaka (Clinics in Colon and Rectal Surgery, 2013)
The construction of an intestinal stoma is fraught with complications and should not be considered a trivial undertaking. Serious complications requiring immediate reoperations can occur, as can minor problems that will subject the patient to daily and nightly distress. Intestinal stomas undoubtedly will dramatically change lifestyles; patients will experience physiologic and psychologic detriment with stoma-related problems, however minor they may seem. Common complications include poor stoma siting, high output, skin irritation, ischemia, retraction, parastomal hernia (PH), and prolapse. Surgeons should be cognizant of these complications before, during, and after stoma creation, and adequate measures should be taken to avoid them. In this review, the authors highlight these often seen problems and discuss management and prevention strategies.
Keywords: stomal complications; ileostomy complications; colostomy complications; enterostomal therapy; wound ostomy continence